Fabrication and optoelectronic characterisation of lanthanide- and metal-ion-doped DNA thin films. (22nd June 2018) - Dugasani, Sreekantha Reddy; Paulson, Bjorn; Ha, Taewoo; Jung, Tae Soo; Gnapareddy, Bramaramba; Kim, Jang Ah; Kim, Taesung; Kim, Hyun Jae; Kim, Jae Hoon; Oh, Kyunghwan; Park, Sung Ha
Abstract: DNA molecules doped with lanthanide and metal ions possess distinct functionalities, providing a feasibility to be utilised in various applications in nano- and biotechnologies. In the present work, we fabricate DNA thin films doped with seven different lanthanide ions (Ce 3+, Dy 3+, Eu 3+, Gd 3+, Tb 3+, Tm 3+, and Sm 3+ ) and four different metal ions (Cu 2+, Ni 2+, Zn 2+, and Co 2+ ) by the drop-casting method. In addition, we conduct current, Hall transport, optical transmittance, and Raman spectroscopic measurements to investigate their electrical properties, carrier concentrations and Hall mobilities, optical band gaps, and vibrational and stretching modes, respectively. By analysing the current–voltage characteristics of the doped thin films with varying dopant concentrations, characteristic critical concentrations are observed, which are related to the significant enhancement of the thin film's physical properties, compared with the pristine DNA. The extrema of the carrier concentrations and Hall mobilities of the doped thin films were observed approximately at the same critical concentrations. The optical band gaps gradually decreased with an increasing dopant concentration, caused by the intrinsic characteristics of both the dopants and DNA. Because of the preference of ions binding to DNA backbones through an electrostatic attraction and to bases via intercalation, the Raman band intensities gradually increase (or decrease) until reaching [Ln]C (or [M]C ), where their trend is reversed. Ln-DNA and M-DNA thin films provide significant, specific, and novel physical characteristics which can be used in various applications.